(untitled) (Nigerian Journal of Technology, 2002)
An experimental study was made of the hygroscopic characteristics as well as the response of yam (D.SPP) tuber to a curing treatment prior to storage. The results indicate that the yam tuber possesses a sigmoidal isotherm dominated by the local isotherm LI – II. The yam tissue responds favorably to proper curing conditions, which generated a well – developed periderm that is impermeable to moisture and resistant to penetration by pathogens. Microscopic studies showed that interruption of tissue continuity by mechanical injury stimulates physical and chemical processes in the cells of which structural re-differentiation is one visible expression. In 20 weeks, properly cured samples lost about 28 per cent total weight while tubers which did not receive any treatment lost as much as 41 per cent of initial weight in the same time interval.